Investigating the correlation between students' perception of authenticity in assessment and their academic achievement in the associated assessment tasks. (1st March 2021) - Ghosh, Samrat; Brooks, Benjamin; Ranmuthugala, Dev; Bowles, Marcus
Abstract: The objective of this research was to investigate the factors of assessment that students undergoing authentic assessment perceived to be significant regarding their academic achievement. This project advanced past research by the authors which found that the academic achievement of seafarer students was significantly higher in a formatively implemented authentic assessment compared with a summative traditional assessment. The academic achievement (assessment scores) was based on the students' performance in analysing information presented in a real-world context (authentic assessment) as opposed to the analysis of information presented devoid of a real-world context (traditional assessment). Using the data obtained from students undergoing the authentic assessment, this project correlated their perceptions of authenticity for factors of assessment to their scores in the associated task. Stage 1 focused on deriving the factors conceptually from the definition of the authentic assessment by the authors, based on which a perception survey questionnaire was designed. Stage 2 extracted new factors through a factor analysis conducted using the software SPSS. Both stages of investigation found that the factor of transparency of criteria was a significant predictor of the students' academic achievement.